Novice Language Teachers’ Emotions in Team-Teaching Practice: A Higher Education Context - Hidayatulloh, Sibakhul Milad Malik; Sudarmiati, Erli Wahyuningtiyas; Ramadhani, Alma Huwaida (Universitas Pendidikan Mandalika, 2025)
Since its presence, team-teaching becomes one of most preferable methods used in language teaching, particularly in higher education context. This current study aims to explore novice language university teacher emotions during the practice of team-teaching in higher education level. By inviting four novice lecturers in one of public universities in East Java, Indonesia, the data were obtained using an in-depth interview. Through several data analysis, dominant emotions and the source of it are identified. Dominant positive emotions were found like relaxed and confidents as the consequences of team-teaching. As for negative emotions, worried, boredom, and confusion appeared as the dominant negative emotions in the obtained data analysis results. Further, the source of positive emotions came from several events, for instance, the sufficient coordination with the team partner, the absence of team partner in the class, and the clear as well as equal distributions of the work inside and outside the class. Negative emotions’ sources, on the other hand, appeared in some events and sources, including the generation gaps between novice teachers and senior teachers as main teachers in the class, joining class without no participation, impromptu questions given by team partner, and the outdated teaching materials and methods. From the analysis, this research is able to give broader and detail context on the teacher emotions in higher education in team-teaching nuances. Finally, the findings from this current research also provides implications and suggestion to the future researchers.